2017
DOI: 10.17219/acem/66837
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters in patients with prostate cancer, benign prostatic hyperplasia and asymptomatic inflammatory prostatitis: A prospective controlled study

Abstract: Background. The imbalance between oxidant and reductant mechanisms creates a nidus for the etiopathogenesis of several diseases. In this study, we aimed to compare the oxidative stress (OS) parameters in patients who were diagnosed with prostate cancer (pCa), benign prostatic hyperplasia (BPH) or asymptomatic inflammatory prostatitis (AIP), according to the histopathologic examination of transrectal ultrasonographic prostate biopsy and transurethral prostate resection specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
1
25
0
3
Order By: Relevance
“…The reason cited for the depletion of the antioxidant enzymes, such as CAT, SOD, and GSH, in BPH has been the accumulation of superoxide anion radicals and hydrogen peroxide (Özten‐Kandaş & Bosland, ). Improving antioxidant status in patients improved clinical signs of BPH (Kaya et al, ; Udensi & Tchounwou, ). Malondialdehyde is produced as a stable product of the free radical peroxidation of cellular organelles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason cited for the depletion of the antioxidant enzymes, such as CAT, SOD, and GSH, in BPH has been the accumulation of superoxide anion radicals and hydrogen peroxide (Özten‐Kandaş & Bosland, ). Improving antioxidant status in patients improved clinical signs of BPH (Kaya et al, ; Udensi & Tchounwou, ). Malondialdehyde is produced as a stable product of the free radical peroxidation of cellular organelles.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of BPH has not been entirely detected. Different factors, including inflammatory mediators, hormones, and oxidative stress, may have a role in the development of BPH (Kaya et al, ). Oxidative stress has been found to be among the mechanisms which activate the factors involved in the development and progression of prostatic hyperplasia (Pace et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interest in this topic was reinforced by a number of recent studies which, besides pointing to an increase in risk of developing prostate cancer in men with a history of chronic prostatitis, demonstrated that oxidative stress is associated with the development and progression of prostate cancer. 18 27 …”
Section: Introductionmentioning
confidence: 99%
“… 122 Due to its properties, curcumin can play a very important role, especially in consideration of newly acquired knowledge indicating that chronic prostatitis favors the development of prostate cancer. 18 25 , 27 …”
Section: Introductionmentioning
confidence: 99%